2015
DOI: 10.21608/adjalexu.2015.59142
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Arthrocentesis With or Without Using Piroxicam in the Management of Temporomandibular Joint Disorders

Abstract: Introduction: Temporomandibular joint dysfunction (TMD) is a clinically significant condition which can be a source of acute or chronic orofacial pain and dysfunction including limitation of mandibular movement. Arthrocentesis is joint lavage which washes out these inflammatory mediators, thereby, relieving pain. Objective: To evaluate the efficacy of arthrocentesis with and without the injection of piroxicam on TMD. Materials and methods: This study was conducted on twenty patients with clinical and radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 17 publications
8
14
0
Order By: Relevance
“…In this study eighteen patients were females & two patients were males with age range varied from 25 to 50 years with a mean age range of 33.8±8.05. In agreement with many studies which concluded that women had a significantly higher prevalence of clinical signs (23)(24)(25). In other studies, female sex seemed to be an increased risk factor for TMD pain (26).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study eighteen patients were females & two patients were males with age range varied from 25 to 50 years with a mean age range of 33.8±8.05. In agreement with many studies which concluded that women had a significantly higher prevalence of clinical signs (23)(24)(25). In other studies, female sex seemed to be an increased risk factor for TMD pain (26).…”
Section: Discussionsupporting
confidence: 93%
“…However, there is a difference between these two methods. The purpose of arthrocentesis is to reduce the negative pressure in disc through the lavage and wash out the inflammatory mediators (24,25). On the other hand, PRP injection focuses on the induction of functional recovery by means of regenerating weakened tissues (27), and its anabolic effect on synoviocytes lead to restore HA levels there by enhancing cartilage protection and joint lubrication (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study, showed postoperative significant difference in MIO, lateral and protrusive movement between group-A and group-B. This finding supported by several clinical studies (17,18,21), suggested that the arthrocentesis produces improvement in all clinical outcomes in a selected group of patients, especially when supplemented by intra-articular injection. Recent studies in basic science done by Reeves et al (22), and Vankdoth et al (35), who reported that the dextrose applied via the intraarticular route causing a stimulation of the chondrogenic effect of intra-articular tissue; Hauser et al (36), suggested that the dextrose has independent effects that may promote local healing of chronically injured extraarticular and intra-articular tissue through stimulating different pathways.…”
Section: Discussionsupporting
confidence: 85%
“…In both studied groups, the arthrocentesis used normal saline was done as following: (18)(19)(20). The surgical field was draped and painted with Betadine (contains povidoneiodine USP 7.5% W/V.…”
Section: Operative Phasementioning
confidence: 99%
See 1 more Smart Citation